All for education : sharing strategies and experiences : panel proceedings... - Naik, Chitra ed. (UNESCO ParisFR, 1993)
Discusses the need to involve the entire population in the achievement of the goals of primary education for all children from the planning stages to the implementation. Looks at India's attempts to achieve primary education for all.